Optical asymmetric JTC cryptosystem based on binary phase modulation and image superposition-subtraction operation - Liu, Yijie; Shen, Xueju; Zhou, Bing; Liu, Jie; Cai, Jianjun; Liu, Xun; Cheng, Yue (Applied optics. Optical technology and biomedical optics, 2022)
The joint transform correlator (JTC) cryptosystem is a simple and practical optical cryptosystem. But its identical key in both encryption and decryption brings security risks in the key distribution and management. To overcome these drawbacks, we first create a trapdoor one-way function based on image superposition and subtraction operation. Then combined with the one-way binary phase modulation, an optical asymmetric JTC cryptosystem is proposed in this paper. These two kinds of trapdoor one-way functions are not only effective and implementable, but also can greatly enhance the ability of our proposal to resist various attacks. In addition, we select the structured spiral phase mask (SSPM) controlled by its structural parameters as the key mask of the JTC cryptosystem to facilitate the key transmission. When the structural parameters of the SSPM are protected by the RSA algorithm during encryption and decryption, not only the security of the proposed cryptosystem can be enhanced, but also the key distribution and management will be improved. This also makes our proposal conform more closely to the basic agreement of the public key cryptosystem. Simulation analysis and initial experimental results verified the correctness and feasibility of our proposal.The joint transform correlator (JTC) cryptosystem is a simple and practical optical cryptosystem. But its identical key in both encryption and decryption brings security risks in the key distribution and management. To overcome these drawbacks, we first create a trapdoor one-way function based on image superposition and subtraction operation. Then combined with the one-way binary phase modulation, an optical asymmetric JTC cryptosystem is proposed in this paper. These two kinds of trapdoor one-way functions are not only effective and implementable, but also can greatly enhance the ability of our proposal to resist various attacks. In addition, we select the structured spiral phase mask (SSPM) controlled by its structural parameters as the key mask of the JTC cryptosystem to facilitate the key transmission. When the structural parameters of the SSPM are protected by the RSA algorithm during encryption and decryption, not only the security of the proposed cryptosystem can be enhanced, but also the key distribution and management will be improved. This also makes our proposal conform more closely to the basic agreement of the public key cryptosystem. Simulation analysis and initial experimental results verified the correctness and feasibility of our proposal.